PERCEPÇÃO DOS USUÁRIOS SOBRE A PRESTAÇÃO DOS SERVIÇOS DE UM RESTAURANTE UNIVERSITÁRIO DE UMA UNIVERSIDADE PÚBLICA DA REGIÃO NORTE DO BRASIL - Azevedo Izel, Patricia; Pinha Gaspar, Lívia; Vieira da Costa, Geraldo (LINKSCIENCEPLACE, 2016)
Many people choose restaurants to make, at least, one of their meals because of the lifestyles in big cities and socioeconomic aspects. At the universities there are restaurants called R.U, where the meals are sold to symbolic prices for academics, and also being a place of interaction and relaxation for users. Due to these factors, this paper aims to present the users' perceptions about service quality offered by a restaurant located in a Public University in the North Region of Brazil. The perspective of this research is qualitative case study type, using semi-structured interviews, respecting the ethical aspects. The data analysis and interpretation are made from the analysis of content strategy. The results show that the restaurants users have high expectation about the environment, service, food and price, but they believe its performance is still below of what they consider as ideal.